Heritology as a general theory of Heritage & The Cybernetic Museum - Šola, Tomislav (2003)
In the circumstances of the endangered world, collective memory and the inherited collective experience appropriated new relevance. They are expected to offer quality input necessary in development, specially the sustainable one. This cybernetic input is the new importance but also an evidence of common basis, the area of resonance. Differing by their practical methods, all the heritage institutions face the same problems and answers in constant try to understand the concept and the meaning of heritage, its role in the society.
Projekt MZOS
ENG